Comparison of Post-Operative Periodontal Pocket Depth After Mandibular Third Molar Surgical Extraction by Using Envelop Flapand Modified Triangular Flap (Medical Forum Monthly, 2023)
Objective: To find out risk factor and their relation to severity of disease in COVID-19 patients.Study Design: Cross sectional prospective studyPlace and Duration of Study: This study was conducted at the Al-Tibri Medical College Hospital, Isra University Karachi campus Karachi from July 2021 to December 2021.Materials and Methods: This cross-sectional prospective study assessed consecutive patients with suspected COVID-19 infection, confirmed by positive RT-PCR. Medical history, clinical and lab evaluations were conducted to determine infection risk factors and disease severity. Patients were categorized into three groups based on symptom severity. Monitoring, management, and follow-up were performed accordingly for all subjects.Results: Total 178 subjects were included in the study. Among those 127 (71.3%) were males and 51 (28.7%) females with over all mean age of 48.062±14.796 years (range 16-85 years). Demographically; majority of subjects were: illiterate or primary education status 60 (33.7%) 59 (33.1%) respectively, sindhi were 75 (42.1%) followed by Baloch 72 (40.4%). On the basis of potential exposure risk: 163 (91.6%) were related non-medical professionally, 37 (20.9%) had exposure history COVID-19 patients, 56 (31.5%) with Mosque attendance, abroad travel history was found in only 19 (10.7%) patients. Disease severity wise; 36 (20.2%) subjects were asymptomatic (Group I), 129 (72.5%) mildly symptomatic (Group II) while 13 (7.3%) patients has severe disease (Group III)Majority of study subjects had one or more Co-morbid/s, among those 26 (14.6%) were diabetics, 22 (12.4%) hypertensive, 29 (16.3%) had both Diabetes and hypertension, 05 (2.8%) bronchial asthma, 03 (1.7%) with ischemic heart disease, 02 (1.1%) had past history pulmonary tuberculosis and 12 subjects had history of disorder other than those common diseases while 79 (44.4%) subjects had no history of any co-morbid.Conclusion: Our study highlighted the advanced age in demographics and hemoglobin, raised TLC, D-Dimer and ferritin are significant laboratory risk factors of severe COVID 19 infection but disparity in literature exist. Hence further studies on larger scale are required to confirm these observations which can be helpful in prediction the severity, prognosis and of course management of disease.